2013
DOI: 10.3141/2380-08
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet–k Nearest Neighbor Vehicle Classification Approach with Inductive Loop Signatures

Abstract: In this study, a new vehicle classification algorithm was developed with inductive loop signature technology. There were two steps to the proposed algorithm. The first step was to use the Haar wavelet to transform and reconstruct inductive vehicle signatures, and the second step was to group vehicles into FHWA vehicle types through the use of the k nearest neighbor (KNN) approach with a Euclidean distance classifier. To determine the proper proportion of the wavelet to apply for reconstruction and feature extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…RTVC-2 Performance Evaluation [14] TABLE I provides the RTVC-2 classification results by FHWA vehicle classification scheme. It was found that classification rates were lower for those classes with smaller sample size in the signature template library.…”
Section: B Rtreid-2m Performance Evaluation [5]mentioning
confidence: 99%
See 3 more Smart Citations
“…RTVC-2 Performance Evaluation [14] TABLE I provides the RTVC-2 classification results by FHWA vehicle classification scheme. It was found that classification rates were lower for those classes with smaller sample size in the signature template library.…”
Section: B Rtreid-2m Performance Evaluation [5]mentioning
confidence: 99%
“…These measures can be further analyzed by vehicle type or by lane to yield even more detailed travel information if required. Furthermore, it is also shown that ILD signature technology possesses the ability to distinguish between passenger and commercial vehicle classes in the FHWA (Federal Highway Administration) vehicle classification scheme [14]- [18], [23]. …”
Section: A Inductive Loop Detector (Ild) Signature Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The Inductive Loop Detectors (ILDs) are sensors widely used in traffic management systems (see works [1], [2], [3], [4]). For such purposes there exist different implementations of ILDs.…”
Section: Introductionmentioning
confidence: 99%